Business Development in Renewable Energy (Case Study: Independent Power Plant (IPP) of Marine Current Turbine PT T-Files Indonesia - Setiawan, Barick Ahmad; Sumirat, Erman (The Indonesian Journal of Business Administration, 2013)
Abstractâ€” Indonesia is experience a surplus in generating capacity of up to 27TWh by 2014 and makes this country struggling to provide electricity for its currents needs that sometimes give delays in capacity development (including with Independent Power Producer (IPP) projects). There are around 20 million households, or 80 million people, who currently have no access to public electricity. This study intends to find out what renewable energy in Indonesia in accordance with the potential that exists with case studies ocean current turbine power plant owned by PT T-Files Indonesia. This plant uses Gorlov turbine with a permanent magnet generator. Specifically this study aims to determine the feasibility of ocean current turbine power plants can be private power plants that sell electricity to PT PLN (Persero) to meet the electricity demand in Indonesia. Calculation of the cost of electricity per kilowatt-hour sales done in the conventional way with the ABCD method is the removal of the component C fuel component. Eligibility is done by searching IRR, NPV and PP from the power plant. Thus obtained if the power plant is feasible or not. Feasibility of the calculation found that the power plant is feasible electricity sales. Plan implementation is done by making 1-year period and electricity sales contracts for 15 years. It can be concluded that the development of electricity generation from renewable energy is feasible for IRR, NPV and PP meet.Â Keywords: business development, renewable energy, power plant, marine current